An Economic Analysis of Joint Production Between Latex and Wood Among Rubber Smallholders in Melaka - Muhammad Afzal, (1998)
The total land devoted to rubber crop (Hevea brasiliensis) in 1995 was estimated to be around 1.7 million hectares, which were about 31 percent of the total land under agricultural crops in Malaysia. The increasing demand in the furniture market and the projected shortage of general utility timber from natural forests has made rubberwood a major source of timber. Malaysian Furniture Industry Council estimated about 80 percent of furniture exports were made up of rubberwood, amounting around RM1.7 billion of total 1996 furniture exports from Malaysia. The global demand for natural rubber is also projected to increase from the present figure of approximately 5.9 million tonnes to around 7.5 million tonnes by the early years of the next century. Latex and rubberwood production can be increased significantly by improving the productivity per unit area, which is very low. The present study was therefore conducted with the objective to find out the extent of increase in latex and rubberwood production through reallocation of resources optimally. The study was conducted in Melaka State, confined to the district of Alor Gajah. All the group replanting (TSB) and mini-estate (ME) schemes yielding latex were sampled. The data were collected by the survey method. Personal interview was used. A sample of 31 holdings comprising 18 TSBs and 13 MEs was selected for this study. Thirty-four sample plots were established for tree measurements to estimate rubberwood yield. The study was confined only to smallholders as about 84 percent of the total area planted with rubber in Malaysia come under smallholdings. Data obtained were subjected to statistical analysis. The frontier production function was buih by imposing a Cobb-Douglas type specification on the frontier and an output-based measure of efficiency was evolved. The maximum revenue combination of latex and rubberwood was determined on the production possibility frontier. A comparison of marginal value products of the variable inputs with their corresponding per unit costs exhibited a potential of 24 percent increase in latex and rubberwood production through optimal resource allocation. It was concluded from the study that optimum combination of latex and rubberwood outputs in conjunction with optimal resource allocation and technically efficient management could increase smallholder's income up to 39 percent. It is suggested that Rubber Industry Smallholders Development Authority should declare latex a by-product, tapped only when it could fetch a good price. In developing rubber sma1lholding sector, the Authority should focus on the mini-estate programme rather than any other scheme. Furthermore, it is also suggested that the Authority should launch a programme for the logging of rubber plantations above 19 years, which are uneconomical to maintain.